2022
DOI: 10.3390/jcm11010238
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Lymphadenopathy on Ultrasound after COVID-19 Vaccination and Its Influencing Factors: A Single-Center Study

Abstract: Purpose: This study aimed to assess the incidence of axillary lymphadenopathy on ultrasound after COVID-19 vaccination and to investigate the factors affecting lymphadenopathy. Methods: We evaluated patients who had received a COVID-19 vaccination within 12 weeks before an ultrasound examination between August and October 2021. The incidence of vaccine-related ipsilateral axillary lymphadenopathy was evaluated using ultrasound. Age, sex, presence of axillary symptoms, injection site, vaccine type, interval fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…On the other hand, some AEs, including Bell's palsy, myocarditis/pericarditis, convulsions/seizures, lymphadenopathy, and anaphylaxis, exhibited a high incidence in young people. In the previous studies, lymphadenopathy [12] and myocarditis/pericarditis [13] have been reported with a higher frequency in the younger population. This study also showed more frequency of inflammation-related AEs such as Bell's palsy, myocarditis/pericarditis, lymphadenopathy, which seemed to estimate high in young people.…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, some AEs, including Bell's palsy, myocarditis/pericarditis, convulsions/seizures, lymphadenopathy, and anaphylaxis, exhibited a high incidence in young people. In the previous studies, lymphadenopathy [12] and myocarditis/pericarditis [13] have been reported with a higher frequency in the younger population. This study also showed more frequency of inflammation-related AEs such as Bell's palsy, myocarditis/pericarditis, lymphadenopathy, which seemed to estimate high in young people.…”
Section: Discussionmentioning
confidence: 84%
“…Unfortunately, the true number of false positive characteristics due to post-COVID-19 vaccination remains unclear because no tissue sampling was performed. In addition, they reported significantly more frequent lymphadenopathy post-COVID-19 vaccination after mRNA vaccine (Comirnaty, Spikevax) when compared to a vector vaccine (Vaxzevria) [17] . On the other hand, in a cohort of 24 patients with lymphadenopathy at physical examination, Cocco et al found no differences in the frequency of lymphadenopathy among different COVID-19 vaccines (Comirnaty, Vaxzevria and Spikevax, respectively) detected at US [18] .…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, a significantly greater cortical thickness was observed in patients without a previous history of COVID-19 pneumonia. Park et al demonstrated lymphadenopathy post-COVID-19 vaccination in 49% of the healthy women referred to a breast cancer unit within 12 weeks after vaccination in a cohort of 413 women [17] . Unfortunately, the true number of false positive characteristics due to post-COVID-19 vaccination remains unclear because no tissue sampling was performed.…”
Section: Methodsmentioning
confidence: 99%
“…In asymptomatic healthy women without risk of metastatic lymphadenopathy, imaging–detected unilateral axillary lymphadenopathy on the same side of the recent COVID-19 vaccination (i.e., within 12 weeks) should be classified as a benign finding, and no further workup should be recommended [ 11 ]. According to published articles on COVID-19 vaccine-associated lymphadenopathies, the most frequently observed morphological characteristics include enlarged lymph nodes with uniform cortical thickening > 3 mm and increased numbers of enlarged lymph nodes [ 12 13 ]. It is more commonly observed within a time interval of 4 weeks after receiving COVID-19 mRNA vaccines than after receiving vector vaccines [ 13 ].…”
mentioning
confidence: 99%